2008
DOI: 10.1088/0268-1242/23/12/125034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal annealing on structural and optical properties of the GaAs0.963Bi0.037alloy

Abstract: We have investigated the effect of thermal annealing on GaAs 0.963 Bi 0.037 layers grown by atmospheric pressure metalorganic vapour phase epitaxy. High resolution x-ray diffraction (HRXRD) patterns show high crystalline quality and remarkable stability against thermal annealing up to 700 • C. When the annealing temperature reaches 750 • C, the GaAs 0.963 Bi 0.037 alloy is no longer stable, and the HRXRD pattern reveals the presence of other peaks. Atomic force microscopy images show a surface accumulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…There are a number of annealing studies reported and they are summarized in Table 5 below. Most previous reports focus on RTA of GaAsBi grown by both MBE [141,[143][144][145][146][147] and MOCVD [148,149]. The growth temperature used is between 200 and 420 • C measured by a thermocouple.…”
Section: Thermal Stability and Bi Diffusionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a number of annealing studies reported and they are summarized in Table 5 below. Most previous reports focus on RTA of GaAsBi grown by both MBE [141,[143][144][145][146][147] and MOCVD [148,149]. The growth temperature used is between 200 and 420 • C measured by a thermocouple.…”
Section: Thermal Stability and Bi Diffusionmentioning
confidence: 99%
“…Moussa et al [148] reported RTA on 25-50 nm thick GaAs 0.963 Bi 0.037 grown by MOCVD. The XRD pattern shows no change up to 700 • C for 900 s while the 10 K PL reveals an enhancement of integrated PL intensity by more than 10 times and a reduction of FWHM from 126 meV to104 meV.…”
Section: Thermal Stability and Bi Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10] Adding small amounts of Bi to the GaAs lattice leads to a large reduction of the band gap, enabling access to important wavelengths in the infrared region. However, the successful incorporation of Bi within the GaAs lattice requires the use of unconventional growth procedures, such as growth temperatures near or below 400 C and a strict control of the As flux.…”
Section: Introductionmentioning
confidence: 99%
“…9 The PL peak wavelength also blue-shifted by 8 meV which was attributed to the micro-scale changes inside the epilayer rather than Bi out diffusion. 9 For metal-organic vapor phase epitaxy (MOVPE) grown GaAs 1-x Bi x , PL intensity improvement of more than 10 times and full-width-at-half-maximum (FWHM) reduction of 23 meV were observed at 10 K. 10 Despite the significant improvements in Ref. 10, no PL emission could be detected above 100 K. Recently, photo-reflectance measurement performed by Chine et al shows that the band gap of GaAs 1-x Bi x was red-shifted by 60 meV after annealing at 600 C.…”
mentioning
confidence: 99%